2004
DOI: 10.1002/polb.20300
|View full text |Cite
|
Sign up to set email alerts
|

Stress–strain behavior of low‐density polyethylene/poly(methyl methacrylate) blends with modulated interfaces with a hydrogenated polybutadiene‐block‐poly(methyl methacrylate) diblock copolymer

Abstract: The stress-strain diagrams and ultimate tensile properties of uncompatibilized and compatibilized hydrogenated polybutadiene-block-poly(methyl methacrylate) (HPB-b-PMMA) blends with 20 wt % poly(methyl methacrylate) (PMMA) droplets dispersed in a low-density polyethylene (LDPE) matrix were studied. The HPB-b-PMMA pure diblock copolymer was prepared via controlled living anionic polymerization. Four copolymers, in terms of the molecular weights of the hydrogenated polybutadiene (HPB) and PMMA sequences (22,000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…However at higher loading, filler–filler interactions are dominated leading to high stress concentration in the PVC matrix due to poor dispersion. This results in decreased elongation at break .…”
Section: Resultsmentioning
confidence: 99%
“…However at higher loading, filler–filler interactions are dominated leading to high stress concentration in the PVC matrix due to poor dispersion. This results in decreased elongation at break .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to electrical conductivity, rheological percolation in immiscible polymer blends is only achieved if the percolated polymer constitutes the major phase or, at least, significantly contributes to the bulk rheology of the blend. A well-known example of the above mentioned improved performance derived from immiscible polymer blends would be the increased toughness of brittle matrices with rubbers or poly(olefin)s or, inversely, the promotion of enhanced tensile strength in elastomers filled with a brittle polymer [12].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…These polymers, which have traditionally been used as commodity plastics, have lately found application in the manufacture of products with high added value [12]. Very few studies have been reported on PMMA/PE blends filled with carbon-based conductive particles (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[10][11][12]20 In this work, a PE/PMMA blend with PMMA as the dispersed phase was targeted in an effort to improve the blend properties by using a "random" copolymer compatibilizer. In a binary blend of PE/PMMA (80/20), clear macrophase separation was observed.…”
Section: Polymer Blend Compatibilizationmentioning
confidence: 99%
“…Interestingly, with the use of PEMMA-3 copolymer that has the lowest MMA mole percent, the elastic modulus of the compatibilized blend was nearly a factor of 2 larger than the binary blend (up to 170 MPa) while still retaining high elongation-at-break values (e.g., 780%) ( Table 2). 20 Mechanical Properties of PEBA-Based Elastomers Mechanical properties of the PEBA samples were also evaluated by uniaxial extension experiments. Figure 5a shows representative tensile tests for PEBA-12.5 and PEBA-6.5.…”
Section: Polymer Blend Compatibilizationmentioning
confidence: 99%